THE RELATIONSHIP BETWEEN SYSTEM OF CLASSIFICATION, SELECTION OF SYMBOLS, AND SYSTEM OF PROHIBITIONS - Soehardi Soehardi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1999)
every society, whether it is simple or conplex, we always find some systems of classification . The basic type of classification is dichotomous partition, i .e . all things in the human and natural world are split into two groups, such as moieties, binary opposition of good and evil in Java or yin-yang in China . Concomittant with the basic classification, in some societies we might still find other classification of triadic categories, of four-sections, of five-classes, of seven -groups, and of nine-divisions . The preliminary purpose of classification is to simplify all things in the human environment.